Philosophy in Prisons Intellectual Virtue and the Community of Inquiry. - Pritchard, D.
This paper describes a pilot study devoted to developing the teaching of philosophy within prison education in Scotland. The study paired the CoPI (community of philosophical inquiry) approach to learning and teaching with a set of educational resources created around a high-profile MOOC (massive open online course) that introduced students to core topics in philosophy. The primary goal of the study was to determine the extent to which the teaching of philosophy in prisons in this specific manner could enhance the intellectual virtues, and thereby the intellectual character, of the students. The results that were collected suggested that the project generated significant success on this front. In addition, the study had a further consequence, which had not been anticipated, in that it also helped the students to develop important personal and interpersonal skills, and thereby also enhanced their character more generally.